ESTIMULAÇÃO COGNITIVA PARA PESSOAS IDOSAS INSTITUCIONALIZADAS: RELATO DE EXPERIÊNCIA - Ramos, José Lúcio Costa; Lima, Elisabete Cleise Schindler; Bomfim, Aiara Nascimento Amaral; Paixão, Isabela Gomes da; Silva, Luciane Souza da (Revista Baiana de Enfermagem‏, 2013)